Design of Brain Activity Measurement for Brain ECVT Data Acquisition System - Edison, Rizki Edmi; Rohmadi, Rohmadi; Pratama, Sra Harke; Ihsan, Muhammad Fathul; Saputra, Almusfi; Purwo Taruno, Warsito (International Journal of Innovative Research in Medical Science, 2021)
Brain Electrical Capacitance Volume Tomography (ECVT) has been developing as an alternative non-invasive brain imaging method. In this study, brain ECVT consisting of two channels, namely a capacitance sensor, is investigated. As a comparison, EEG sensor is used to measure brain activity simultaneously with the brain ECVT. Brain activity measurements were carried out at the pre-frontal lobe of Fp1 and Fp2 locations. The resulting signal was processed by filtering method and Power Spectral Density (PSD). The result of signal analysis shows that the measurement between EEG and ECVT shows the same activity of the two modalities.